Structural model of quality of life based on perceived stress with the mediating role of personality traits in women with premenstrual syndrome - Yasaman Shahjoei; Taher Tizdast; Mohammadreza Zarbakhsh (مجله علوم روانشناختی)
Background: Research evidence indicates that women with premenstrual syndrome do not have a good quality of life and mention several factors as predictors of this. There is a research gap regarding the role of perceived stress and personality traits in the quality of life of these women, Therefore, addressing the mentioned variables in the form of a structural model on women with premenstrual syndrome seems necessary. Aims: The purpose of this research was to present a structural model of quality of life based on perceived stress with the mediating role of personality traits in women with premenstrual syndrome. Method: The research method was descriptive-analytical of structural equation modeling. The statistical population of this research included all women referred to counseling clinics and psychological services, health centers and gynecologists' offices diagnosed with premenstrual syndrome in the western areas of Tehran between January 2021 to March of 2022. Among the women of the statistical population, 419 women were selected by convenience sampling method. Data collection tools in this research include questionnaires of Premenstrual Symptoms Screening Tool (Steineret al., 2003), Perceived Stress (Cohen et al., 1983), quality of life (Ware & Sherbourne, 1992) and the the shortened version is the NEO Five-Factor Inventory (Costa & McCrae, 1989). To analyze the research data, Pearson correlation methods and structural equation modeling were used with the help of SPSSV-25 and AMOSV-24 software. Results: The results showed the relationship between neuroticism and perceived stress was positive and with quality of life, negative and significant, but other personality traits had a negative relationship with the components of perceived stress and a positive and significant relationship with the components of quality of life (P<0.01). Also, the effect of perceived stress on quality of life was negative and significant (P<0.01). In addition, among the personality traits, the effect of the path coefficient between conscientiousness, agreeableness and extraversion on quality of life and neuroticism on quality of life was negative and significant (P<0.01). In addition, the indirect path coefficient between perceived stress and quality of life through conscientiousness, neuroticism and extroversion was also negative and significant (P<0.01). Conclusion: According to the findings of this research, it can be said that the quality of life model of women with premenstrual syndrome has a favorable fit, Therefore, the awareness of specialists in the fields of psychology, counseling and health of this model can be very effective and helpful in improving the quality of life of this category of women.